The Cocoa Farming Through Agricultural Extension: Effects on Competence and Productivity - Managanta, Andri Amaliel; Hardini, Nuraini Siti (Universitas Negeri Gorontalo, 2025)
The non-formal education process aims to support farmers in enhancing their agriculture skills and achieving mutual interdependence. Enhancing the involvement of extension workers is believed to positively influence farming productivity. This study seeks to identify the role of extension in cocoa commodities and to examine the factors affecting the productivity improvement of cocoa farmers. The research was carried out in cocoa-producing areas, in Poso Regency. The sample size in this study was determined using Partial Least Square (PLS) analysis, following the minimum requirement of five times the number of research indicators, resulting in a total of 103 respondents. Data were analyzed through descriptive statistics and Structural Equation Modeling (SEM) using the Partial Least Square (PLS) approach with the Smart-PLS program. Factors such as farmer characteristics and the role of extension workers have a significant impact on improving farmer competency. Farmer competency can be improved through the role of extension workers based on the specific needs of cocoa farmers. This increase in competency has a direct impact on increasing farmer production and income. Farmers with higher competency will be able to optimize the use of agricultural inputs, such as the use of fertilizers and pesticides, and be more effective in various processes, such as cultivation, harvesting, post-harvest, processing, and marketing.